Systems Biology and Biotechnological Analytics for Disease Management and Environmental Remediation - Qasim Salih, Noor Imad; Ghawei, Tahseen Ali Wadi; Hanwan, Zahraa Sayed; Jawad, Hussein Ali Saadoun (American Journal of Biology and Natural Sciences, 2025)
Systems Biology explores the structure and dynamics of complex biological systems from a holistic perspective. Its development in the mid-20th century transformed it into a comprehensive scientific discipline focused on understanding biological processes through integration of biological, medical, engineering, and computational technologies . Concurrently, Biotechnology utilizes microbes, plants, and animals to develop medicinal products, new vaccines, and environmentally friendly solutions such as pollutant degradation and enhanced disease resistance in plants and animals. Systems approaches address challenges across various scientific domains, enabling collaborative efforts to develop innovative and sustainable methods for disease management and environmental remediation, supported by biotechnological analytics.